2000
DOI: 10.1111/j.1447-0756.2000.tb01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Contraception in Diabetic Women: Comparative Metabolic Study of Norplant, Depot Medroxyprogesterone Acetate, Low Dose Oral Contraceptive Pill and CuT380A

Abstract: In diabetics, Norplant results in minimal metabolic alterations followed by OCs while DMPA has unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 16 publications
0
20
0
3
Order By: Relevance
“…In a comparative study of norplant and depot medroxyprogesterone acetate (DMPA) in diabetic women, it was found that norplant caused only minimal metabolic changes whilst DMPA was associated with more unfavourable changes [16]. In a comparison of two implants, implanon ® containing etonogestrel (the active metabolite of desogestrel) and norplant containing levonorgestrel acetate, both preparations resulted in similar small effects on the hemostatic system, which were not suggestive of a tendency towards thrombosis [17].…”
Section: Injectable Progestinsmentioning
confidence: 96%
“…In a comparative study of norplant and depot medroxyprogesterone acetate (DMPA) in diabetic women, it was found that norplant caused only minimal metabolic changes whilst DMPA was associated with more unfavourable changes [16]. In a comparison of two implants, implanon ® containing etonogestrel (the active metabolite of desogestrel) and norplant containing levonorgestrel acetate, both preparations resulted in similar small effects on the hemostatic system, which were not suggestive of a tendency towards thrombosis [17].…”
Section: Injectable Progestinsmentioning
confidence: 96%
“…Likewise, Diab and Zaki found that fasting blood glucose was higher among users of oral contraceptives and Depo-Provera (depot-medroxyprogesterone acetate, DMPA), a progestogen-only reversible hormonal contraceptive injected every 3 months (9). After reviewing these studies, we hypothesized that an increased risk for GDM would be observed among women who had used hormonal methods of contraception.…”
Section: Introductionmentioning
confidence: 99%
“…However Diab reported increase in fasting blood sugar in females maintained on OCs and DMPA when compared to Norplant on long term use. This study concluded that in diabetics, Norplant caused minimal metabolic alterations followed by OCs whereas DMPA has unfavorable outcome 10 .…”
Section: Resultsmentioning
confidence: 80%